A Well‐Mixed Phase Formed by Two Compatible Non‐Fullerene Acceptors Enables Ternary Organic Solar Cells with Efficiency over 18.6%. Issue 33 (10th July 2021) - Cai, Yunhao; Li, Yun; Wang, Rui; Wu, Hongbo; Chen, Zhihao; Zhang, Jie; Ma, Zaifei; Hao, Xiaotao; Zhao, Yong; Zhang, Chunfeng; Huang, Fei; Sun, Yanming
Abstract: The ternary strategy, introducing a third component into a binary blend, opens a simple and promising avenue to improve the power conversion efficiency (PCE) of organic solar cells (OSCs). The judicious selection of an appropriate third component, without sacrificing the photocurrent and voltage output of the OSC, is of significant importance in ternary devices. Herein, highly efficient OSCs fabricated using a ternary approach are demonstrated, wherein a novel non‐fullerene acceptor L8‐BO‐F is designed and incorporated into the PM6:BTP‐eC9 blend. The three components show complementary absorption spectra and cascade energy alignment. L8‐BO‐F and BTP‐eC9 are found to form a homogeneous mixed phase, which improves the molecular packing of both the donor and acceptor materials, and optimizes the ternary blend morphology. Moreover, the addition of L8‐BO‐F into the binary blend suppresses the non‐radiative recombination, thus leading to a reduced voltage loss. Consequently, concurrent increases in open‐circuit voltage, short‐circuit current, and fill factor are realized, resulting in an unprecedented PCE of 18.66% (certified value of 18.2%), which represents the highest efficiency values reported for both single‐junction and tandem OSCs so far. Abstract : Highly efficient organic solar cells are fabricated using a ternary approach, wherein a novel non‐fullerene acceptor L8‐BO‐F is designed and incorporated into the PM6:BTP‐eC9 blend. L8‐BO‐F and BTP‐eC9 are found to form a homogeneous mixed phase, which improves the molecular packing of both donor and acceptor materials, and optimizes the ternary blend morphology. A record‐high efficiency of 18.66% is consequently achieved.